2019
DOI: 10.1097/gme.0000000000001362
|View full text |Cite|
|
Sign up to set email alerts
|

Age at natural menopause and physical functioning in postmenopausal women: the Canadian Longitudinal Study on Aging

Abstract: Objective:The aim of this study was to evaluate the association between categories of age at natural menopause (ANM) and gait speed (slowness) and grip strength (weakness), common measures of physical functioning in older women.Methods:We analyzed data from the Canadian Longitudinal Study on Aging, which included participants from seven cities across Canada collected in 2012. The sample was restricted to women who reported to have entered menopause (N = 9,920). Women who had a hysterectomy before menopause wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 47 publications
2
27
2
2
Order By: Relevance
“…30 Height-adjusted step length was significantly shorter for women beyond 65 years old, but height-adjusted cadence did not differ significantly from early adulthood till 75 years old. Beyond that, the compound effect of accentuated declines in both 31 which has been reported to cause a slowing gait. 32 This could possibly explain for the gradual gait speed decline of our female participants beyond 50 years old.…”
Section: Discussionmentioning
confidence: 97%
“…30 Height-adjusted step length was significantly shorter for women beyond 65 years old, but height-adjusted cadence did not differ significantly from early adulthood till 75 years old. Beyond that, the compound effect of accentuated declines in both 31 which has been reported to cause a slowing gait. 32 This could possibly explain for the gradual gait speed decline of our female participants beyond 50 years old.…”
Section: Discussionmentioning
confidence: 97%
“…We used covariates that may influence the association between circuit training and BW: BMI status (obesity vs overweight vs normal weight), intervention type (circuit training alone intervention vs circuit training combined with other lifestyle interventions), age (≥50 vs <50 years), intervention period (≥6 vs <6 months), and sex (men vs women vs men and women). The cut‐off for age (50 years) was based on age at natural menopause and andropause . The cut‐off for the intervention period (6 months) was based on prior reviews .…”
Section: Methodsmentioning
confidence: 99%
“… 1 Studies of Western populations have shown that approximately 10% of women undergo menopause prior to the age of 45, resulting in a significantly decreased premenopausal estrogen exposure duration relative to women with later-onset menopause. 2 , 3 Muka et al 4 conducted a meta-analysis which revealed an elevated risk of cardiovascular disease (CVD) and mortality among women who undergo early-onset menopause (<45 years).…”
Section: Introductionmentioning
confidence: 99%